2021
DOI: 10.1039/d0sc06096h
|View full text |Cite
|
Sign up to set email alerts
|

The central role of the metal ion for photoactivity: Zn– vs. Ni–Mabiq

Abstract: Photoredox catalysts are integral components of artificial photosystems, and have recently emerged as powerful tools for catalysing numerous organic reactions. However, the development of inexpensive and efficient earth-abundant photoredox catalysts...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…32,46,47,159,160 In parallel, considerable progress has been made toward 3d 8 MLCT luminophores based on Ni II , though in this case the breakthrough has not yet been made in the sense that room-temperature MLCT emission has not been achievable until now. 49,109 A paradigm change occurred with the recent emergence of highly emissive two-coordinate Cu I complexes which are LLCT luminophores (Figure 7b), [37][38][39]42,45 and with the discovery of Mn IV and Fe III LMCT emitters (Figure 7a). 29,30,119 The reversal of the charge transfer direction when going from MLCT to LMCT has direct consequences for possible applications in dye-sensitized solar cells; 161 yet as far as the luminescence properties are concerned, LMCT or LLCT emitters seem highly competitive with MLCT luminophores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,46,47,159,160 In parallel, considerable progress has been made toward 3d 8 MLCT luminophores based on Ni II , though in this case the breakthrough has not yet been made in the sense that room-temperature MLCT emission has not been achievable until now. 49,109 A paradigm change occurred with the recent emergence of highly emissive two-coordinate Cu I complexes which are LLCT luminophores (Figure 7b), [37][38][39]42,45 and with the discovery of Mn IV and Fe III LMCT emitters (Figure 7a). 29,30,119 The reversal of the charge transfer direction when going from MLCT to LMCT has direct consequences for possible applications in dye-sensitized solar cells; 161 yet as far as the luminescence properties are concerned, LMCT or LLCT emitters seem highly competitive with MLCT luminophores.…”
Section: Discussionmentioning
confidence: 99%
“…Other new developments in Ni II photochemistry involve the use of macrocyclic ligands, but no emission has been reported so far. 108,109 4. LMCT EMITTERS: 3d 0 (Sc III ), 3d 3 (Mn IV ), 3d 5 (Fe III ), AND 3d 6 (Co III ) COMPLEXES Energetically low-lying LMCT states call for electron-rich ligands and electron-deficient metals.…”
Section: Llct Emitters: 3d 10 (Cu I ) Complexesmentioning
confidence: 99%
“…One of us has previously developed the solution chemistry of a series of mono- and bimetallic Mabiq complexes. Monometallic M-Mabiq complexes (e.g., M = Fe, Co, Ni, Cu, and Zn) with formal oxidation states ranging from 0 to III were isolated. Our studies demonstrated that both the mono- and bimetallic compounds are photoactive. , Notably, the Co-Mabiq complex acts as an electrocatalyst for H 2 evolution, while Ni-Mabiq enables photocatalytic C–C bond formation. , …”
Section: Introductionmentioning
confidence: 78%
“…37−41 Our studies demonstrated that both the mono-and bimetallic compounds are photoactive. 41,42 Notably, the Co-Mabiq complex acts as an electrocatalyst for H 2 evolution, 43 while Ni-Mabiq enables photocatalytic C−C bond formation. 40,42 The tethering of Mabiq molecules on well-defined solid supports has not yet been explored.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation